Roman Noir, Modernism and Revolution in Paco Ignacio Taibo II’s Shadow of the Shadow (2006)
This article studies the way in which Paco Ignacio Taibo dissects the cultural and historical context that shaped the Mexico of the first two decades of the 20th century in his novel Sombra de la sombra. A tireless advocate of the «neopolicíaco», Taibo tu